A Study on Reasons for Initiation and Frequency of Smoking Among Rural Population in Dehradun District of Uttarakhand - Danish Imtiaz; Sunit Dutt Kandpal; Ruchi Juyal (Medsci Publications, 2016)
Background: Tobacco is a major public health problem all over the world with 82% of the world's 1.1 billion smokers residing in low and middle income countries. The study was conducted to find the reasons for initiation and frequency of smoking tobacco used among rural population. Methodology: Present study was conducted in the rural field practice area of Department of Community Medicine, Himalayan Institute of Medical Sciences, Dehradun. The households were selected by systematic random sampling and all the smoking tobacco users were personally interviewed using a pre-structured and pretested schedule. Results: Overall, 663 current smokers was found in the study. Peer pressure (31.2%) was the most common reason for initiating smoking in the surveyed population. Majority (88.8%) of the current daily male smokers were smoking upto 10 cigarettes per day. Majority of the males (60.8%) were smoking more than 10 bidi per day; while majority (77.3%) of the females were smoking upto 10 bidis per day. Conclusion: In the study Peer pressure was found to be the most common reason for initiating smoking. Cigarette smoking is considered as a taboo in society as revealed by no female cigarette smoker in the study.